Enthalpies of formation of monoderivatives of hydrocarbons: Interaction of polar groups with an alkyl group - Exner, Otto; Böhm, Stanislav (Journal of computational chemistry, 2004)
Energies of hydrocarbon monoderivatives CH(3)X, C(2)H(5)X, n-C(4)H(9)X, and n-C(5)H(11)X with 16 different substituents X were calculated at the levels B3LYP/6-311+G(d,p) and B3LYP/AUG-cc-pVTZ//B3LYP/6-311+G(d,p). The results were used to test the validity of the additive rule that has served commonly for estimating the enthalpies of formation Delta(f)H(T). The exact additivity corresponds to zero reaction energy DeltaE of the isodesmic reaction, in which the substituent X is transferred from one alkyl group R to another. Additivity is approximately fulfilled for butyl and pentyl derivatives with the differences less than 0.3 kJ mol(-1) (except charged groups X). Methyl derivatives deviated from the additive rule up to 22 kJ mol(-1) for dipolar groups X and 45 kJ mol(-1) for charged group, in agreement with the available experiments and with the anticipation of all suggested empirical schemes. In addition, smaller deviations of ethyl derivatives (3 or 20 kJ mol(-1), respectively) were observed here for the first time. There is no correlation between the deviations of methyl and ethyl derivatives; they are also not related to steric effects, and only partly to polarization. Deviations of methyl derivatives are proportional to the electronegativity of the first atom of the substituent; even when the definition of electronegativity is somewhat questionable, one can say in any case that it is controlled by the first atom.